Hubungan Profitabilitas terhadap Pembayaran Zakat Bank Umum Syariah di Indonesia - Dwi Santosa Pambudi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The social function of Islamic banks is in accordance with the company's compliance with paying zakat. However, the amount of corporate zakat payments by Islamic banks is strongly influenced by the level of profitability. Therefore, the purpose of this study is to investigate the relationship between profitability and zakat payment for Islamic banks. The population of this study includes all Islamic Commercial Banks totaling 14 units. The sampling technique used purposive sampling method. Profitability variables are seen from the ratio of ROA and zakat payments are seen from company zakat with multiple linear regression analysis. The research findings show that the level of profitability represented by ROA has a negative relationship to the zakat paid by Islamic commercial banks